To what extent do fiscal regimes equalize opportunities for income acquisition among citizens? - John E. Roemer; Rolf Aaberge; Ugo Colombino; Johan Fritzell; Stephen P. Jenkins; Ive Marx; Marianne Page; Evert Pommer; Javier Ruiz-Castillo; Maria Jesus San Segundo; Torben Tranaes; Gert G. Wagner; et al. (University of Essex, Institute for Social and Economic Research (ISER), 2000)
This projeect employs the theory of equality of opportunity, described in Roemers (Equality of Opportunity), Havard University Press, 1998), to compute the extent to which tax-and-transfer regimes in ten countries equalize opportunities among citizens for income acquisition. Roughly speaking, equality of opportunity for incomes has been achieved in a country when it is the case that the distributions of post-fisc income are the same for different types of citizen, where a citizens type is defined by the socio-economic status of his parents. Intuitively, a country will have equalized opportunity if the changes of earning high (or low) income are equal for citizens from all family backgrounds. Of course, pre-fisc income distributions, by type, will not be identical, as long as the educational system does not entirely make up for the disadvantage that children, who come from poor families face, but the tax-and-transfer system can play a role in rectifying. We include, in our computation, two numbers that summarize the extent to which each countrys current fiscal regime achieves equalization of opportunities for income, and the deadweight loss that would be incurred by moving to the regime that does.
Keywords: 330